1991
DOI: 10.1038/bjc.1991.21
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the growth promoting properties of ascitic fluids, cyst fluids and peritoneal fluids from patients with ovarian tumours

Abstract: Summary The growth promoting properties of ascitic fluids, cyst fluids and peritoneal fluids from patients with ovarian malignancy, benign ovarian tumours and non-tumour related gynaecological conditions have been investigated using an ovarian carcinoma cell line (OAW 42) (La Rocca & Rheinwald, 1985). Materials and methods Patient groupsAscitic fluids were collected from ovarian cancer patients (n = 42), non-ovarian cancer patients (n = 13), non-tumour patients (n = 4) and one patient with a benign ovarian tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Only 6 of our 36 ascites samples had detectable TGF-· levels. Arteaga et al [10] showed that 42% of their ovarian cancer patients' effusions (approximately 25% of the samples were pleural fluid) had detectable TGF-· by RIA, while Wilson et al [19] could find no TGF-· in any of their ascites samples. TGF-· is initially translated as a 160-amino acid trans-membrane precursor which then undergoes proteolytic cleavage by a sequence-specific protease found external to the cell membrane releasing the 50-amino acid TGF-·.…”
Section: Discussionmentioning
confidence: 99%
“…Only 6 of our 36 ascites samples had detectable TGF-· levels. Arteaga et al [10] showed that 42% of their ovarian cancer patients' effusions (approximately 25% of the samples were pleural fluid) had detectable TGF-· by RIA, while Wilson et al [19] could find no TGF-· in any of their ascites samples. TGF-· is initially translated as a 160-amino acid trans-membrane precursor which then undergoes proteolytic cleavage by a sequence-specific protease found external to the cell membrane releasing the 50-amino acid TGF-·.…”
Section: Discussionmentioning
confidence: 99%
“…Cystic fluid production takes part in both malignant and benign pathologies of ovary. These fluids have been shown to contain factors that influence the growth of ovarian carcinoma cells and the transformation of mesothelial cells ( 19 ) . HGF is known to be produced by mesenchymal originated cells and effects the neighboring epithelial originated cells.…”
mentioning
confidence: 99%
“…An unknown growth factor has been postulated to be responsible for the elevated growth‐stimulating activity on the ovarian carcinoma cell line HEY in the ascitic fluids of ovarian carcinoma patients, but not those of patients with other gynecologic carcinoma or benign ovarian tumors 1. The activity that transforms mesothelial cells in ascites, cyst fluids, and peritoneal fluids in patients with ovarian malignancy, benign diseases, and non‐tumor‐related gynecological conditions were compared, and the elevated activity was found to be tumor‐associated 2. The active principle in the former was later identified as lysophosphatidic acid (LPA),3 but the structure of the active principle in the latter remains obscure.…”
mentioning
confidence: 99%